Pengaruh Service Quality, Diferensiasi Produk, Student Preference dalam Memilih Perguruan Tinggi Swasta Institut Teknologi dan Bisnis Tuban Mediasi Citra Kampus - Silvy Dewi Anggraini; Titin; Nurul Badriyah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Abstract: This research aims to examine the influence of Service Quality dimensions (Servqual) and Differentiation Concurrent Pes Student Preference in selecting private higher education institutions, specifically Institut Teknologi dan Bisnis Tuban, with Campus Image as a mediator. The study employs a quantitative method with inferential quantitative hypotheses. The population consists of all ITB Tuban students in the 2023/2024 academic year, with a sample size of 111 students. The analytical technique used in this research is Partial Least Squares (PLS). By using the outer model to test validity and reliability. As well as aninner model to test hypothesis. The results indicate that Differentiation Of Concurrent Pes (X2) through Campus Image (Z) on Student Preference (Y) has a coefficient of 0.029 with a T-value of 0.722 and a P-value of 0.470, indicating non-significance. This implies that Differentiation Of Concurrent Pes does not significantly affect Student Preference through Campus Image. In contrast, the mediation path of Service Quality (X1) through Campus Image (Z) on Student Preference (Y) has a coefficient of 0.171 with a T-value of 2.696 and a P-value of 0.007, indicating significance. This signifies that Service Quality significantly influences Student Preference through Campus Image, suggesting that improvements in Service Quality will enhance Campus Image and subsequently increase Student Preference.